Solar Thermal Power: Appraisal of Solar Power Towers - Shatnawi Hashem; Lim Chin Wai; Ismail Firas Basim (MATEC Web of Conferences, 2018)
This study delves into several engineering procedures related to solar power tower plants. These installations come with central receiver system technologies and high-temperature power cycles. Besides a summary emphasizing on the fundamental components of a solar power tower, this paper also forwards a description of three receiver designs. Namely, these are the tubular receiver, the volumetric receiver and the direct absorber receiver. A variety of heat transfer mediums were assessed, while a comprehensive explanation was provided on the elements of external solar cylindrical receivers. This explanation covers tube material, molten salt, tube diameter and heat flux.